Thermal plasticity deformation buckling analysis on the carbon fiber-reinforced aluminum matrix composite material. Issue 2 (April 2021) - Huang, Xiupei; Li, Zhuoyun
As light weight and durability have become the important design objectives for the modern aircraft structures, the carbon fiber-reinforced resin matrix composites are widely applied to the aircraft structures for it can reduce the airframe weight effectively at the same time of guaranteeing the load-carrying capacity. In aircraft structures, the mechanical connection remains the important connection pattern for the composite material and the laminated structures; however, existence of the connecting hole has resulted in the stress concentration of structures while the borehole fatigue breakdown of parts is the main failure mode of aircraft structures. According to the low fatigue life of the aircraft connection structures, research on the hole extrusion and reinforcement technology on the carbon fiber-reinforced composite material and the laminated structure is made in this paper.